Observational assessment of surgical teamwork: a feasibility study. - Undre, S; Healey, A; Darzi, A; Vincent, C (2006)
BACKGROUND: Teamwork is fundamental to effective surgery, yet there are currently no measures of teamwork to guide training, evaluate team interventions or assess the impact of teamwork on outcomes. We report the first steps in the development of an observational assessment of teamwork and preliminary findings. METHOD: We observed 50 operations in general surgery from a single operating theater using a measure of teamwork specifically developed for use in the operating theater. The OTAS (Observational Teamwork Assessment for Surgery) comprises a procedural task checklist centered on the patient, equipment and communications tasks and ratings on team behavior constructs, namely: communication, co-operation, co-ordination, shared-leadership and monitoring. RESULTS: Ratings of overall team performance were reasonably high, though variable, but there was evidence that clinically significant steps were being missed which at the very least eroded safety margins. There was, for instance, a frequent failure to check both surgical and anesthetic equipment and a failure to confirm the procedure verbally, patient notes were missing in about one-eighth of the cases and delays or changes occurred in over two-thirds of the cases. CONCLUSIONS: This study takes an initial step towards developing measures of team performance in surgery that are defined in relation to tasks and behaviors of the team. The observational method of assessment is feasible and can provide a wealth of potentially valuable research data. However, for these measures to be used for formal assessment, more research is needed to make them robust and standardized.